Racial Differences in Tobacco Cessation and Treatment Usage After Lung Screening: An Examination of the National Lung Screening Trial. (28th December 2015) - Kumar, Pallavi; Gareen, Ilana F.; Lathan, Christopher; Sicks, JoRean D.; Perez, Giselle K.; Hyland, Kelly A.; Park, Elyse R.
Abstract: Background: Black smokers have demonstrated greater lung cancer disease burden and poorer smoking cessation outcomes compared with whites. Lung cancer screening represents a unique opportunity to promote cessation among smokers; however, little is known about the differential impact of screening on smoking behaviors among black and white smokers. Using data from the National Lung Screening Trial (NLST), we examined the racial differences in smoking behaviors after screening. Methods: We examined racial differences in smoking behavior and cessation activity among 6, 316 white and 497 black (median age, 60 and 59 years, respectively) NLST participants who were current smokers at screening using a follow-up survey on 24-hour and 7-day quit attempts, 6-month continuous abstinence, and the use of smoking cessation programs and aids at 12 months after screening. Using multiple regression analyses, we examined the predictors of 24-hour and 7-day quit attempts and 6-month continuous abstinence. Results: At 12 months after screening, blacks were more likely to report a 24-hour (52.7% vs. 41.2%, p < .0001) or 7-day (33.6% vs. 27.2%, p = .002) quit attempt. However, no significant racial differences were found in 6-month continuous abstinence (5.6% blacks vs. 7.2% whites). In multiple regression, black race was predictive of a higher likelihood of a 24-hour (odds ratio [OR], 1.6, 95% confidence interval [CI], 1.2–2.0) and 7-day (OR, 1.5, 95% CI, 1.1–1.8) quit attempt; however, race was not associated with 6-month continuous abstinence. Only a positive screening result for lung cancer was significantly predictive of successful 6-month continuous abstinence (OR, 2.3, 95% CI, 1.8–2.9). Conclusion: Although blacks were more likely than whites to have 24-hour and 7-day quit attempts, the rates of 6-month continuous abstinence did not differ. Targeted interventions are needed at the time of lung cancer screening to promote abstinence among all smokers. Abstract : Racial differences in smoking behavior and cessation among National Lung Screening Trial participants who were current smokers at screening using a follow-up survey were evaluated. Although blacks were more likely than whites to attempt to quit, the rates of continuous abstinence did not differ. Targeted interventions are needed at the time of lung cancer screening to promote abstinence among all smokers.